Fuel effects on operability of aircraft gas turbine combustors - Colket, Meredith; Heyne, Joshua (American Institute of Aeronautics and Astronautics, 2021)
Alternative jet fuel has been an active area of research and development since the 1973 oil embargo. Research goals have included establishing energy security, lowering fuel costs, and reducing emissions with a focus on developing cost-effective methodologies for processing and sustaining jet fuel production from shale, tar sands, coal, biomass, end use waste, and CO2. Physical and chemical properties, such as the viscosity, vapor pressure, boiling range, free.
Keywords: Jet engines -- Combustion chambers.; Jet planes -- Fuel.; Fuel switching.; elektronické knihy; electronic books